KEEFEKTIFAN SISTEM PELATIHAN MODA DARING BERTAHAP TERHADAP UPAYA PENINGKATAN KOMPETENSI MAHASISWA SEBAGAI PENYELIA HALAL: STUDI EVALUASI - Susanti, Evi Susanti (FKIP Universitas Wisnuwardhana, 2023)
The research is aimed to measuring the effectiveness of training on student competencies as halal supervisors. Research respondents as many as 42 participants. The effectiveness of the training was analyzed using the Kirkpatrick level 1 (response) and level 2 (learning outcomes) models. The results of the first level evaluation showed that participants gave a positive response to the training materials and training methods that were carried out online gradually. In the second level evaluation (learning outcomes), it was found that participants were able to receive more than 50% of the training materials, both in stage I, stage II, and stage III training. Based on these results, gradual online mode training can be recommended as an alternative effective training method to improve student competence.